Implementasi Sosial Media Marketing dalam Mendukung Kegiatan Pemasaran Pavin Block Berbahan Baku Sampah Plastik Kelompok “Lestari Bumi” Purbalingga - Santoso, Muhammad Hery; Martiani, Evi; Mutiasari, Mutiasari; Rahmawati, Herni Utami; Hasanah, Nurul (Universitas Nusantara PGRI Kediri, 2022)
This community service project works with partners, that is Kelompok Lestari Bumi, a pavin block manufacturing company made from plastic waste. This company was founded by a group of Jetis village residents in Kemangkon district of Purbalingga district who were concerned about the growing amount of plastic waste in their community and how it was affecting the environment. In order to do that, they attempt to transform it into pavin bricks, a product that is both practical and valuable economically. The challenge Kelompok Lestari Bumi is in the area of marketing, where word-of-mouth advertising is still used, making the product less well known to the general population. In reality, given the product's originality, high quality, and competitive pricing, especially considering that the raw material is plastic trash, it may have advantages. In order to carry out community service, a variety of techniques are used, including: (1) identifying partners' marketing limitations; (2) developing solutions to partners' issues; and (3) providing partners with training and mentorship. Digital marketing using Facebook's social media network has been proposed as the solution. The outcomes that are anticipated are: (1) increased online product promotion with a larger audience through Facebook social media; (2) reduced marketing expenses; and (3) improved long-term sales performance.